Correlation between Aryl Hydrocarbon Receptor with Hepatic and Renal Function Tests in Fuel Filling Station Workers - Muthana S. Mashkour (Journal of Global Pharma Technology, 2018)
The exposures to gasoline and gas oil, for a long time, in the gas stations through inhalation of vapors during refueling are generally hazardous. Gasoline consists of different types of aliphatic hydrocarbons and aryl compounds. Aryl hydrocarbon receptor (AHR) is a receptor involved in the regulation of biological responses to planar aromatic hydrocarbons. The aim of the present study is to compare the serum AHR level in the fuel station workers (FSW) with the non-workers as a control group. The other aim is to find out a possible correlation between AHR with liver and kidney function tests. Sixty male FSW and 30 controls, from ten fuel stations at Al-Najaf City-Iraq, were participated in the present study. The AHR levels were measured using ELISA technique. Other parameters (urea, creatinine, total serum bilirubin (TSB), alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), and albumin) were measured spectrophotometrically by using ready for use kits. Serum concentration of AHR, ALT, AST and Creatinine in FSW group revealed a significant increase (p<0.001) as compared with the control group. No significant difference was noticed in other parameters. There were significant increase in AST (p=0.002) and ALT (p<0.001) in exposure ≥12yrswith exposure <12yrs in FWS. Smoking has no significant correlation with other parameters. Correlation study indicated a correlation between AHR and Age. No correlation noticed between AHR and any measured parameters in FWS.  It can be concluded that, AHR estimation is important in FSW in order to monitor the health of liver and kidney in those workers.Keywords: Aryl Hydrocarbon Receptor, Liver, Kidney, Fuel Filling Workers.